PENGEMBANGAN MEDIA PEMBELAJARAN E-LEARNING BERBASIS EDMODO PADA MATA PELAJARAN PRAKARYA KEWIRAUSAHAAN KELAS X SMA - Sharfina, Genclang (Jurnal Pendidikan Teknik dan Vokasional, 2021)
The purpose of this study was to develop Edmodo-based learning media in SMA Negeri 17, Bekasi City. The method used in this research is the research and development (R&D) method using the Borg and Gall model. The research was carried out by starting the research stage and information and planning, preliminary development of the product, preliminary field testing, revision of the main product, objectives and implementation. The development stage is carried out in three stages, namely product manufacturing, internal product testing, and product revision. Testing was carried out by 3 experts, namely 2 instructional media experts, and 1 material expert. The results of the study were carried out with the CVR results, stating that learning was very feasible to use, with a percentage of 93% and 100%, and material experts related to learning materials were very feasible to use with a percentage of 90.91%. It was conveyed that the development of Edmodo-based e-learning learning media in PKWU subjects, batik material is suitable to be applied in high school through distance learning, so that it is more supportive of teachers to deliver learning materials well. Keywords: E-Learning, Edmodo, PKWU, Batik